PG38 Using simulation to support doctors' return training: A pilot study. (10th November 2020) - Ellerton, Laura; Keshtkar, Fatemeh; Sharma, Anju; Welfare, E; Shanahan, Toni; Parr, Timothy; Altemimi, Balsam; Mercer, Simon
Abstract : Introduction: Approximately 10% of doctors in postgraduate medical training take time out of programmes annually. 1 An estimated additional 13.5% of doctors stepped back from clinical practice in line with the government's shielding policy from SARS-CoV-2. 2 The shielding guidance has now been relaxed leading to many practitioners returning to the clinical environment. 2 The Department of Health has allocated £10 million annual funding for initiatives to support doctors returning to clinical practice. 1 SuppoRTT has been developed as a national resource to aid returning clinicians following Health Education England's (HEE) ten commitments to support trainees with their return to training. 1 As part of the SuppoRTT resources for HEE, in January 2020 a pilot simulation course was designed, piloted and evaluated with the intention to build confidence and refresh key clinical concepts in those returning to clinical practice. Method: The course consisted of a one-day fully immersive simulation experience based at our institution. Junior doctors from emergency medicine and acute medical specialities participated in multiple common hospital-based high-fidelity simulation scenarios that were set in the emergency department. An immediate video assisted debrief focussed on the fears and concerns of the candidates as well as their clinical competency. A short survey was completed by all course attendees to explore their thoughts on the use simulation as an adjunct to other resources in returning to training. Results: Seven doctors attended the pilot course following an extended period away from training. Over 70% (5/7) of candidates cited their main motivation for attending the course was to build confidence. The attending doctor's concerns regarding their return to training were varied and often centred around fears of incompetence. Following attendance, candidate's confidence increased on average 2 points (using a scale of 1 to 10) and unanimously met their self-derived learning needs. Secondary outcomes were that candidates expressed relief at meeting peers in similar situations and discussing their issues within a safe environment. Conclusions: Fully immersive simulated clinical scenarios allow doctors who have been away from training for a prolonged period of time to build their confidence in a safe and supported environment. Candidates particularly benefited from working and talking with other who were also in the same situation and supported each other through the day. Our course is now being fully developed and incorporated into the local HEE SuppoRTT programme. The recent pandemic has emphasised the importance in supporting colleagues returning to the workplace. References: Health Education England. SuppoRTT. [Online]. Available from: https://www.hee.nhs.uk/our-work/supporting-doctors-returning-training-after-time-out [Accessed 27 August 2020]. BMA. BMA COVID tracker survey full results 2020. [Online]. Available from: https://www.bma.org.uk/media/3070/bma-covid-tracker-survey-full-results-aug-2020.pdf [Accessed 27 August 2020].